2002
DOI: 10.1096/fj.02-0092fje
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons present in cigarette smoke cause endothelial cell apoptosis by a phospholipase A2dependent mechanism

Abstract: Smoking is a major risk factor for endothelial cell injury and subsequent coronary artery disease. Epidemiological studies implicate the phospholipase A2/arachidonic acid cascade in the mechanism by which smoking causes heart disease. However, specific components of cigarette smoke that activate this pathway have not been identified. The purpose of this study was to investigate the effects of polycyclic aromatic hydrocarbons contained in cigarette smoke on phospholipase A2 (PLA2) activity and apoptosis of huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
48
0
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 45 publications
4
48
0
3
Order By: Relevance
“…This gene encodes cytosolic phospholipase A 2 -α (cPLA 2 -α) playing a central role in the release of arachidonic acid (AA) from sn2 position of membrane phospholipids, and AA metabolism is involved in a number of biological events such as inflammatory and carcinogenic processes. Previous studies revealed that TCDD promoted the release of AA from membranes as a result of its ability to stimulate membrane lipid oxidation and phospholipase A 2 (PLA 2 ) activity (al-Bayati and Stohs, 1991;Forsell et al, 2005;Tithof et al, 1996Tithof et al, , 2002. Therefore, our finding might fill-in the missing link between TCDD stimulation and phospholipase A 2 induction.…”
Section: Discussionsupporting
confidence: 56%
“…This gene encodes cytosolic phospholipase A 2 -α (cPLA 2 -α) playing a central role in the release of arachidonic acid (AA) from sn2 position of membrane phospholipids, and AA metabolism is involved in a number of biological events such as inflammatory and carcinogenic processes. Previous studies revealed that TCDD promoted the release of AA from membranes as a result of its ability to stimulate membrane lipid oxidation and phospholipase A 2 (PLA 2 ) activity (al-Bayati and Stohs, 1991;Forsell et al, 2005;Tithof et al, 1996Tithof et al, , 2002. Therefore, our finding might fill-in the missing link between TCDD stimulation and phospholipase A 2 induction.…”
Section: Discussionsupporting
confidence: 56%
“…3)-formed with either a benzyl (bay region) or alkyl group (bay-like region), were biologically active in the induction of arachidonic acid release, inhibition of GJIC and the activation of mitogen activated protein kinase pathways in a rat liver epithelial cell line with oval cell characteristics. [51][52][53] This structure-activity relationship was also observed in the induction of arachidonic acid release from endothelial cells 54 and the inhibition of GJIC in rat cardiac myocytes. 55 Consistent with these previous observations, 1-methylanthracene, which has a bay-like region, inhibited forskolin-induced GJIC in the H6c7 pancreatic epithelial ductal cells, whereas the linear isomer, 2-methylanthracene, had no effect on GJIC.…”
Section: Discussionsupporting
confidence: 56%
“…Some studies suggest that patients who die of eroded plaque are often smokers . Recently, a study showed that polycyclic aromatic hydrocarbons found in cigarettes could induce human coronary artery endothelial cell apoptosis (Tithof et al 2002). In addition, despite the lack of evidence that turbulent blood flow directly induces endothelial denudation, an in vivo study suggested that there was a systemic preferential occurrence of apoptosis in the downstream parts of plaques, where low flow and low shear stress prevail (Tricot et al 2000).…”
Section: Discussionmentioning
confidence: 99%